Voice of the Voiceless in Olga’s Novel Drive Your Plow - Sigdel, Madhu Sudan (Patan Prospective Journal, 2023)
This article investigates Olga Tokaraczuk’s novel Drive Your Plow Over the Bones of the Dead (2019) from the perspective of welfare of all the life forms other than the human characters in power. It explores the need of conserving all the living beings for their co-existence. As the actions and events go revealing the mysteries of the murders in the novel, the study highlights the need for mutual existence of the species in this earthly environment. The protagonist of the novel gets totally tormented when she comes to know the life forms, as represented by deer, foxes, plants and insects, get tortured due to some so called gentle human’s inhuman behavior. The consciousness of minority people gets shattered when the mainstream leaders undermine their voice. This makes the minority groups unite to make a voice for the voiceless. In the same way, the biotic environment of this world gets hampered when the leaders of mankind become self-centered, violent and unconcerned to other creatures. The author intends to present the protagonist who keeps sincerely performing the responsibilities but rigorously fighting against the evil forces which, as represented by the human leaders, cause harm to all the innocent life forms. So, this study shows the need of establishment of harmony among all the life forms in the society fighting against anti-social behavior of social leaders.